2021
DOI: 10.3389/fchem.2021.761682
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of pH-Responsive, Self-Assembled, Novel Polysaccharide Composite Hydrogel and Its Application in Selective Capture of Cationic/Anionic Dyes

Abstract: Dyes are one of the most hazardous chemicals causing significant environmental pollution and affecting water quality. Majority of the existing methods for dye removal and degradation involve synthetic membranes and use of hazardous chemicals, further resulting in secondary pollution. The present study reports polysaccharide based novel composite hydrogel as biodegradable matrix for pH-responsive selective adsorption of cationic/anionic dyes. This membrane showed pH-responsive adsorption of methyl green (MG) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
(86 reference statements)
0
16
0
Order By: Relevance
“…The presence of oppositely charged polyelectrolytes undergoes strong electrostatic interactions to yield a self-assembled polyelectrolyte complex (PEC). , Hence, the participating polymers must be ionized and possess opposite charges. In the case of natural polysaccharides, chitosan most commonly forms PEC via electrostatic interaction between its positive amino group and opposite negative groups of numerous polyelectrolytes such as alginate, gellan, and κ-carrageenan . Srivastava et al reported PEC formation among a cationic amino group of chitosan along with an anionic carboxylate group of gellan and a sulfate group of κ-carrageenan to fabricate green self-assembled pH-responsive hydrogel .…”
Section: Hydrogel Cross-linking Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of oppositely charged polyelectrolytes undergoes strong electrostatic interactions to yield a self-assembled polyelectrolyte complex (PEC). , Hence, the participating polymers must be ionized and possess opposite charges. In the case of natural polysaccharides, chitosan most commonly forms PEC via electrostatic interaction between its positive amino group and opposite negative groups of numerous polyelectrolytes such as alginate, gellan, and κ-carrageenan . Srivastava et al reported PEC formation among a cationic amino group of chitosan along with an anionic carboxylate group of gellan and a sulfate group of κ-carrageenan to fabricate green self-assembled pH-responsive hydrogel .…”
Section: Hydrogel Cross-linking Methodsmentioning
confidence: 99%
“…47 Moreover, osmotic pressure generated by the electrostatic interaction through ion and counterion movement triggers the swelling capacity of ionic polysaccharides. 29 Due to the natural diffusion of swelling medium into polymers, their porous structure forms capillary channels that account for pH change responses. In contrast, a hydrogel with cationic charges containing a positive pendant group, such as amines, exhibits swelling when the pH falls below the pK b due to protonation responsible for increased electrostatic repulsion.…”
Section: Ph-responsivementioning
confidence: 99%
See 2 more Smart Citations
“…Adsorption is one of the most effective methods to treat organic dyes, and it is widely used because of its relatively low cost and easy operation. Various adsorbents have been designed to remove dyes in water and have considerable adsorption capacities, such as activated carbon ( Tang et al, 2017 ; Zhang et al, 2019 ; Soares et al, 2021 ), functional carbon materials ( Magno et al, 2020 ; Xing et al, 2020 ; Zhang et al, 2020 ), composite hydrogel ( Srivastava and Roy Choudhury, 2021 ), and metal oxide ( Rastogi et al, 2017 ; Xu et al, 2020 ; Şerban and Enesca, 2020 ). Among these methods, chemistry reduction has gained popularity because of its ease of use, high efficiency, clean processing, and low cost.…”
Section: Introductionmentioning
confidence: 99%